Co-existing conjunctival non-Hodgkin's lymphoma and pulmonary sarcoidosis. Issue 4 (April 1996) - Ryan, P J; Stableforth, P; McLeod, D T
Abstract : A 55 year old woman with a conjunctival non-Hodgkin's lymphoma was found to have pulmonary nodules on a thoracic computed tomographic scan which were initially thought to be lymphomatous deposits. A subsequent biopsy specimen demonstrated granulomas consistent with sarcoidosis. The relationship between sarcoidosis and malignancy, in particular lymphoma, is discussed.